2018
DOI: 10.1093/schbul/sby091
|View full text |Cite
|
Sign up to set email alerts
|

Classification of First-Episode Schizophrenia Using Multimodal Brain Features: A Combined Structural and Diffusion Imaging Study

Abstract: Recent neuroanatomical pattern recognition studies have shown some promises for developing an objective neuroimaging-based classification related to schizophrenia. This study explored the feasibility of reliably identifying schizophrenia using single and multimodal multivariate neuroimaging features. Multiple brain measures including regional gray matter (GM) volume, cortical thickness, gyrification, fractional anisotropy (FA), and mean diffusivity (MD) were extracted using fully automated procedures. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 52 publications
4
22
0
Order By: Relevance
“…Posterior limb white matter integrity reductions, measured as fractional anisotropy, were previously reported in a small group of patients with early-stage schizophrenia [47]. Further underscoring the role of this region in the illness, a machine learning based pattern recognition study discovered that fractional anisotropy of the corticospinal tract was one of the most prominent discriminant features separating HC from first-episode schizophrenia patients [48]. Interestingly, the posterior limb of the internal capsule was one of the few white matter regions where no fractional anisotropy abnormalities were detected in chronic schizophrenia patients in a large individual data meta-analysis in conducted by the ENIGMA DTI working group [1].…”
Section: Discussionmentioning
confidence: 74%
“…Posterior limb white matter integrity reductions, measured as fractional anisotropy, were previously reported in a small group of patients with early-stage schizophrenia [47]. Further underscoring the role of this region in the illness, a machine learning based pattern recognition study discovered that fractional anisotropy of the corticospinal tract was one of the most prominent discriminant features separating HC from first-episode schizophrenia patients [48]. Interestingly, the posterior limb of the internal capsule was one of the few white matter regions where no fractional anisotropy abnormalities were detected in chronic schizophrenia patients in a large individual data meta-analysis in conducted by the ENIGMA DTI working group [1].…”
Section: Discussionmentioning
confidence: 74%
“…Cutting-edge machine learning methods have been applied in structural and functional neuroimaging studies and have revealed that multivariate patterns of brain change are sensitive enough to classify individual SCZ patients (Liu et al, 2015;Yuan et al, 2018b). Combining cortical thickness, gyrification of gray matter, and fractional anisotropy and mean diffusivity of white matter, Liang et al (2019) used a gradient boosting decision tree to identify SCZ patients, reaching an average accuracy of 76.54%. Using global and nodal network properties derived from a graph theory analysis, Jo et al (2020) revealed that functional network properties had a high discriminatory ability for classifying SCZ patients and HCs.…”
Section: Discussionmentioning
confidence: 99%
“…Classification algorithms were used to separate the positive samples from the negative ones in each of the four datasets {D(Sc), D(Sp), D(Kl), D(Pp)}. This study utilized five classification algorithms to evaluate their capabilities of predicting DNA replication origins, i.e., support vector machine (SVM) (Weston, et al, 2001), random forest (RF) (Jang, et al, 2018;Li, et al, 2018), multinomial naïve Bayes (MNB) classifier (Pan, et al, 2018), gradient boosting decision tree (GBDT) (Liang, et al, 2018;Wang, et al, 2019), and back propagation neural network (BPNN) (Rumelhart, et al, 1986).…”
Section: Classification Of Dna Replication Originsmentioning
confidence: 99%